Antibody response following Hepatitis B vaccination in peritoneal dialysis patients: does normalized urea clearance matter? (Clinics, 2011)
OBJECTIVES: Data on the factors that contribute to the antibody response to hepatitis B virus vaccination in peritoneal dialysis patients are scarce. The current study was conducted on a group of peritoneal dialysis patients to learn how the response to hepatitis B virus vaccination varies according to the patient's clearance of urea normalized to total body water (Kt/V). METHODS: A convenience sample of 33 peritoneal dialysis patients (13 women and 20 men, with a mean age of 49¡12 years) was administered double doses (20 μg IM in each deltoid muscle) of recombinant hepatitis B vaccine at 0, 1, 2, and 6 months. Response to immunization was measured at one to three months after the final dose of vaccine. The subjects were divided into groups according to the level of antibodies to hepatitis B surface antigen (anti-HBs), including non-responders ( < 10 IU/L), weak responders (10-100 IU/L), and good responders ( > 100 IU/L). RESULTS: Among non-responders, weak responders, and good responders, significant differences were found in age (54 ± 12 vs. 56 ± 9 vs. 45¡12 years, respectively; p = 0.049) and recombinant human erythropoietin use (20 vs. 29 vs. 76%, respectively; p = 0.016). No significant differences in weekly total Kt/V (p = 0.704), weekly peritoneal Kt/V (p = 0.064) and residual glomerular filtration rate (p = 0.355) were found across the three groups. CONCLUSIONS: Delivered clearance measured by weekly peritoneal Kt/V and total clearance measured by weekly total Kt/V did not predict the response to hepatitis B virus vaccination in patients on peritoneal dialysis.